Tiresias como auxiliar de justicia en la antigua Grecia (2020)
Usually when addressing the issue of administration of justice there is a figure who becomes responsible for all activity. Nowadays, society only recognizes justice in the figure of the judge, however it must be understood that it is not the only one that makes up this activity, but in order to achieve its function it requires a whole scaffolding of people, and resources, hence there is an overvaluation, by attributing to one person an activity that belongs to a group of people. However, in the common person only it recognized who is at the forefront of such efforts. In ancient Greece in the same way, it is understood that justice was carried out through the gods, but even the deities required the help of certain people, it is the case of Tiresias who through his interaction between gods and humans becomes an auxiliary of divine justice performing the activities that gods or humans asked him for.